Tanggung Jawab Notaris Dalam Menjaga Kerahasiaan Data Penghadap di Era Digital - Luchia Saldi, Sindi; Rembrandt, Rembrandt; Elda, Edita (Recital Review, 2025)
A notary is a public official who is authorized to make authentic deeds and has other authority as referred to in the Notary Position Law or based on other laws. The Notary has an obligation to keep everything confidential about the deed he makes and all information obtained for the preparation of the deed in accordance with the oath/promise of office, unless the Law specifies otherwise. In maintaining the confidentiality of personal data in the digital era, it is very important considering that personal data can be used by unauthorized parties for various interests, the formulation of the problem in this study is first, how is the legal protection of the confidentiality of the data of the person facing in the digital era, the second is how the role of technology in helping notaries to maintain the confidentiality of the data of the person who is confronted in the digital era, and the third is how is the responsibility of the notary for the confidentiality of the data of the person who is facing in the digital era. The research method used is normative juridical, with a legislative, conceptual and case approach, a type of secondary research, with additional interviews with the Regional Supervisory Council (MPD) of the Padang Region and Notaries in Padang City. The legal protection of the confidentiality of personal data in the digital era aims to ensure that the right to privacy is respected, prevent the misuse of personal data for various purposes, prevent misuse by establishing rules on how personal data can be collected, stored and used. The role of technology in helping notaries to maintain the confidentiality of client data is very crucial in the notary profession, by utilizing various security systems, notaries can provide more optimal protection of the client's personal data. Notary's responsibility for the confidentiality of client data in the digital era of notaries will face various legal and ethical consequences. By understanding their responsibilities and taking preventive measures, notaries can minimize the risks and negative impacts of data leaks. There are no rules regulating the confidentiality of client data and sanctions for notaries if there is a leak of client data in the digital era, creating a void in norms. So that the confidentiality of the data of the person has not been guaranteed.